2018
DOI: 10.1186/s40352-018-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and suicidal behaviour among incarcerated adults in the Australian Capital Territory

Abstract: BackgroundSuicide is the leading cause of death in prisons worldwide. Improved understanding of the factors associated with suicide is necessary to inform targeted suicide prevention and interventions. Here we aim to (a) document the prevalence of suicide attempts, suicidal ideation, self-harm, and mental disorder; and (b) identify demographic, mental health, and criminal justice correlates of suicidal ideation, in a sample of incarcerated adults in Australia.MethodsData were obtained from the 2016 Detainee He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
8
0
3
Order By: Relevance
“…Levels of ACE exposure reported by participants were substantially higher than those measured in the Welsh general population, with 84.4% of male prisoners reporting at least one of the 11 ACEs measured and 45.5% reporting ≥4 ACEs; compared with 46.3% (at least one ACE) and 11.9% (≥4 ACEs) respectively in males in the general population (Hughes et al 2018). Consistent with other international studies (Butler et al 2018), reported levels of lifetime mental illness diagnoses, self-harm or suicide attempt among prisoners were also elevated compared to general population levels (Hughes et al 2018). Despite our study excluding those that were currently being managed due to risk of selfharm or suicide attempt, one in five participants reported lifetime self-harm whilst in prison and one in ten reported lifetime suicide attempt.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Levels of ACE exposure reported by participants were substantially higher than those measured in the Welsh general population, with 84.4% of male prisoners reporting at least one of the 11 ACEs measured and 45.5% reporting ≥4 ACEs; compared with 46.3% (at least one ACE) and 11.9% (≥4 ACEs) respectively in males in the general population (Hughes et al 2018). Consistent with other international studies (Butler et al 2018), reported levels of lifetime mental illness diagnoses, self-harm or suicide attempt among prisoners were also elevated compared to general population levels (Hughes et al 2018). Despite our study excluding those that were currently being managed due to risk of selfharm or suicide attempt, one in five participants reported lifetime self-harm whilst in prison and one in ten reported lifetime suicide attempt.…”
Section: Discussionsupporting
confidence: 82%
“…However, low MWB is associated with vulnerability to mental illness alongside poorer health outcomes and behaviours (Howell et al 2007;Stranges et al 2014). Studies evidence a higher prevalence of current low MWB, mental illness and self-harm amongst those incarcerated than the general population (Fazel et al 2016;Kariminia et al 2007;Tweed et al 2018Tweed et al , 2019, whilst suicide is the leading cause of death in custody globally (Butler et al 2018). In England and Wales, rates of selfharm in the male adult prison population have been increasing, with over 43,000 incidents reported in the year ending September 2018; a rate of 540 incidents per 1000 prisoners (Ministry of Justice 2019).…”
Section: Introductionmentioning
confidence: 99%
“…68 Suicide is the leading cause of death in custody globally and is preventable; hence, it needs to be targeted in this high-risk population. 69 In our study, a minority of women (16.7%) had a previous psychiatric diagnosis and/or treatment for a psychiatric disorder despite the majority having a lifetime history of mental illness. This is in contrast to the study by Tyler et al (UK) who found that a high number of prisoners had previous contact with mental health services or a prior psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 55%
“…Di sisi lain, dukungan sosial dalam penjara dan proses rehabilitasi sosial yang baik dalam penjara juga memainkan peranan yang penting bagi kesehatan mental tahanan (McKay, Comfort, Grove, Bir, & Lindquis t, 2018). Selain itu, bagi tahanan yang tidak mampu dalam menerima dan bahkan menolak realitas penahanannya, maka risiko timbuln ya masalah emosi negatif tadi bahkan muncul dan berdampak lebih lanjut kepada perilaku menyakiti diri dan bunuh diri (Butler, Young, Kinner, & Broschmann, 2018).…”
Section: Upaya Menerima Kenyataanunclassified